Trust Economy in Islamic Healthcare: Building Patient Trust Through Halal Certification and Service Innovation - Astiwara, Endy Muhammad (Universitas Aisyah Pringsewu, 2024)
This study explores the role of the trust economy in Islamic healthcare, focusing on how halal certification and service innovation contribute to building patient trust. Using a Systematic Literature Review (SLR) approach, this research analyzes 50 relevant studies published between 2015 and 2024. The findings reveal that halal certification plays a crucial role in assuring patients of compliance with Islamic principles, thereby enhancing their confidence in healthcare providers. Additionally, service innovations such as halal telemedicine and patient-centered care models significantly impact transparency, patient satisfaction, and loyalty. Studies indicate that hospitals implementing telemedicine solutions see a 40% improvement in service transparency, while those adopting patient-centered approaches report a 35% increase in patient loyalty. Despite these advancements, gaps remain in empirical research on the long-term economic impact of trust-based healthcare systems and the effectiveness of digital trust models. Future research should explore these aspects further and assess the role of policy frameworks in strengthening halal healthcare regulations. Islamic healthcare providers can enhance patient trust and ensure sustainable growth in the sector by integrating ethical, technological, and religious considerations.